THE INTERACTION BETWEEN NATURE AND SOCIETY IN THE WORKS OF WESTERN AND EASTERN WRITERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study provides a comprehensive analysis of the interaction between nature and society in the literature of Western and Eastern writers. Nature is portrayed as a crucial element influencing the social, economic, cultural, and philosophical aspects of human life and society. In Eastern literature, nature is often deeply intertwined with the inner world of humans, their philosophical reflections, and religious beliefs, emphasizing harmony and balance between humanity and the natural world. Conversely, Western literature tends to depict nature as a source of societal development and highlights the impact of human activities on social changes. This paper explores the complex relationship between nature and society across various historical periods and cultural contexts through literary and cultural studies perspectives. Furthermore, it examines how this interaction is expressed through literary devices such as imagery, symbolism, and narrative techniques. The research aims to identify both similarities and differences in the conceptualizations of nature and society by Western and Eastern authors.